Socio-Psychological Characteristics of Young People Returning from Migration - Xamroyev Mansur Choriyevich (International Journal on Integrated Education, 2026)
This article examines the socio-psychological characteristics of young people returning from labor migration in the context of contemporary social and economic changes. Migration processes significantly influence personality development, value orientations, social identity, and psychological well-being of youth. While migration experience often enhances independence, resilience, and adaptability, the return to the home country may be accompanied by serious challenges of social and psychological readaptation. The study analyzes emotional states, self-esteem, communication patterns, and social activity of returnee youth. Particular attention is paid to stress, frustration, feelings of social alienation, and uncertainty regarding future life prospects. The article also highlights the importance of family support, social environment, and institutional assistance in facilitating successful reintegration. The role of psychological services and targeted support programs aimed at minimizing negative psychological consequences of migration experience is emphasized. The findings of the study have practical relevance for psychologists, social workers, educators, and policymakers involved in youth development and migration issues.